2009
DOI: 10.19030/ajbe.v2i6.4092
|View full text |Cite
|
Sign up to set email alerts
|

Selected Private Higher Educational Institutions In Metro Manila: A DEA Efficiency Measurement

Abstract: This paper measures the technical efficiency of 16 selected colleges and universities in Metro Manila, Philippines, using academic data for the SY 2001 2005. Using the data envelopment analysis (DEA), on average, schools posted 0.807 index score and need additional 19.3% efficiency growth to be efficient. Overall, there are top four efficient schools, with an average technical efficiency score between 99-100%, representing 25% of the sample. The slacks and efficient targets results have schools policy decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…For example, many studies have used the number of students or number of enrolments (headcount or full-time equivalent (FTE)) as a teaching output variable (e.g., McMillan & Datta, 1998;Avkiran, 2001;Abbott & Doucouliagos, 2003;Castano & Cabanda, 2007a, b;Bobe, 2009;Guzman & Cabanda, 2009;Cuenca, 2011;Lee, 2011;Agasisti & Lezzi, 2013). Ahn and Seiford (1993) suggested that headcount or FTE enrolment has been popularly used as a major output of institutions of higher learning (IHLs) not only because of data availability, but also because of its direct relation to state funding formulas.…”
Section: The Proposed Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many studies have used the number of students or number of enrolments (headcount or full-time equivalent (FTE)) as a teaching output variable (e.g., McMillan & Datta, 1998;Avkiran, 2001;Abbott & Doucouliagos, 2003;Castano & Cabanda, 2007a, b;Bobe, 2009;Guzman & Cabanda, 2009;Cuenca, 2011;Lee, 2011;Agasisti & Lezzi, 2013). Ahn and Seiford (1993) suggested that headcount or FTE enrolment has been popularly used as a major output of institutions of higher learning (IHLs) not only because of data availability, but also because of its direct relation to state funding formulas.…”
Section: The Proposed Modelsmentioning
confidence: 99%
“…The total income (in billion VND) includes total sources of income from budget, tuition, scientific research and technology transfer activities, and other. In fact, the incorporation of the total income as an output along with the student number was proposed by Castano and Cabanda (2007a, b), Guzman andCabanda (2009) andCuenca (2011). In short, the different variable sets used to measure the efficiency of Vietnamese doctorate-granting universities are summarized in Table 2.…”
Section: The Proposed Modelsmentioning
confidence: 99%
“…A current approach to school evaluation considers the school as production unit that uses multiple inputs (resources) and produces multiple outputs (outcomes). In such a setting, the definition and measurement of the inputs and outputs that reflects the operation of a school for evaluation is not an easy task (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the efficiency of state universities and colleges (SUCs) in the Philippines have been made, and some of these used DEA in their evaluation. The paper by Cuenca (7) looked into the efficiency of SUCs in the whole Philippines using DEA by considering expenditure data as input parameter and number of enrolled students, number of graduates and total revenue for 78 SUCs in the country. The study identified that majority of the SUCs included in the study were less efficient based on the parameters considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation